Technological Transformation in Malaysian Zakat Institutions - Marhanum Che Mohd Salleh; Mohammad Abdul Matin Chowdhury (Center of Strategic Studies (PUSKAS) BAZNAS, 2020)
This research observes technology adoption among zakat institutions in Malaysia. To achieve this objective, a qualitative approach is adopted where the primary data is collected via observation of website or any related materials, which supports technology application among Zakat institutions in Malaysia. The materials including website, the information of online collection or payment system and others. The findings indicate that majority of the zakat institutions have started to utilize technology system in their organization, especially with regards to zakat payment. However, there is still lacking of technology usage for zakat distributions, awareness as well as zakat fund reporting to public. Overall, as zakat collection and distribution have involved millions of records and its management is still questionable by all parties, it is believed that technology will enhance the operations of zakat institutions to become more efficient and effective to distribute wealth to the needy. It is thus public trust towards the institutions is expected to increase.